Literatur Review Peran Administrasi Kesehatan dalam Meningkatkan Kualitas Layanan Kesehatan - Nurcholisah Fitra; Inayyah Nur Fitry (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
This research examines the role of health administration in improving the quality of services in community health centers (Puskesmas). The study aims to assess how well-managed administrative systems can contribute to enhancing service delivery in these facilities. Using a systematic literature review approach, data were collected from a range of academic sources published between 2010 and 2024. The findings highlight that effective health administration, including human resource management, transparent policies, and proper health data management, positively influences service quality. The study also reveals that challenges remain, particularly in areas with limited resources, but that improved administration can mitigate these issues. The implications of these findings suggest that policy makers should focus on strengthening administrative practices at Puskesmas through better resource management and enhanced training for staff. Furthermore, the research offers directions for future studies, recommending more field-based research to validate the relationship between health administration and service quality in varying settings.